2001
DOI: 10.1007/s001250051591
|View full text |Cite|
|
Sign up to set email alerts
|

Advanced glycation end-products: a review

Abstract: Diabetes is a common condition with multiple complications. There has been much work done to elaborate on the aetiology, prevention and treatment of diabetes related complications. The DCCT [1] and UKPDS [2] studies have emphasised the role of tight glucose control as being important in reducing diabetic microvascular disease in Type I (insulin-dependent) diabetes mellitus (DCCT) and Type II (non-insulin-dependent) diabetes mellitus (UKPDS). The relation between tight glucose control and macrovascular complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

20
1,709
3
57

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,216 publications
(1,789 citation statements)
references
References 109 publications
20
1,709
3
57
Order By: Relevance
“…Chronic accumulation of AGEs is accelerated with aging and with aging‐related diseases such as diabetes, hyperlipidemia, and renal disease (Cho et al ., 2009). Advanced glycation end products AGEs may accumulate in vascular tissues, thickening and stiffening vascular walls, and increasing the risk of hypertension (Singh et al ., 2001; Goh & Cooper, 2008). Higher levels of AGEs are associated with cognitive impairment in people with cerebrovascular disease, suggesting a relationship between AGEs and vascular dementia (Southern et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic accumulation of AGEs is accelerated with aging and with aging‐related diseases such as diabetes, hyperlipidemia, and renal disease (Cho et al ., 2009). Advanced glycation end products AGEs may accumulate in vascular tissues, thickening and stiffening vascular walls, and increasing the risk of hypertension (Singh et al ., 2001; Goh & Cooper, 2008). Higher levels of AGEs are associated with cognitive impairment in people with cerebrovascular disease, suggesting a relationship between AGEs and vascular dementia (Southern et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Glycation is the reaction of carbonyl compounds, including glucose, ascorbate oxidation products, and methylglyoxal, that forms a variety of structurally diverse stable adducts in proteins; these adducts are collectively known as advanced glycation endproducts or AGEs (Singh et al ., 2001). Several studies have shown the accumulation of AGEs in the aged BM of the kidneys, lungs, and lens capsule (Bailey et al ., 1993; Oldfield et al ., 2001; Song et al ., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Advanced glycation endproducts form when glucose reacts with the proteins to form unstable Schiff bases, which then undergo further modification to form Amadori products (44,50). Additional rearrangements or modifications may occur giving rise to advanced glycation endproducts seen in prolonged hyperglycemia or aged individuals.…”
Section: Introductionmentioning
confidence: 99%
“…AGEs have been shown to be etiologic factors in diabetes-induced nephropathy, retinopathy, neuropathy, and diabetes-accelerated atherosclerosis (40,44,50). AGEs are also thought to contribute to many of the complications of aging including disorders such as osteoarthritis, cataract formation and changes observed in myocardial dysfunction (6,30,39).…”
Section: Introductionmentioning
confidence: 99%